Human Pluripotent Stem Cell-Derived Neural Cells and Brain Organoids Reveal SARS-CoV-2 Neurotropism Predominates in Choroid Plexus Epithelium - Jacob, Fadi; Pather, Sarshan R.; Huang, Wei-Kai; Zhang, Feng; Wong, Samuel Zheng Hao; Zhou, Haowen; Cubitt, Beatrice; Fan, Wenqiang; Chen, Catherine Z.; Xu, Miao; Pradhan, Manisha; Zhang, Daniel Y.; et al. (Cell stem cell, 2020)
Neurological complications are common in patients with COVID-19. Although severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causal pathogen of COVID-19, has been detected in some patient brains, its ability to infect brain cells and impact their function is not well understood. Here, we investigated the susceptibility of human induced pluripotent stem cell (hiPSC)-derived monolayer brain cells and region-specific brain organoids to SARS-CoV-2 infection. We found that neurons and astrocytes were sparsely infected, but choroid plexus epithelial cells underwent robust infection. We optimized a protocol to generate choroid plexus organoids from hiPSCs and showed that productive SARS-CoV-2 infection of these organoids is associated with increased cell death and transcriptional dysregulation indicative of an inflammatory response and cellular function deficits. Together, our findings provide evidence for selective SARS-CoV-2 neurotropism and support the use of hiPSC-derived brain organoids as a platform to investigate SARS-CoV-2 infection susceptibility of brain cells, mechanisms of virus-induced brain dysfunction, and treatment strategies. [Display omitted] •SARS-CoV-2 minimally infects human neurons and astrocytes in 2D and brain organoids•Model developed for hiPSC-derived choroid plexus organoids (CPOs)•SARS-CoV-2 productively infects CPOs and increases cell death•SARS-CoV-2 CPO infection leads to transcriptional upregulation of inflammatory genes SARS-CoV-2 causes neurological symptoms in a significant portion of patients with COVID-19. Ming and colleagues tested SARS-CoV-2 neurotropism by using monolayer neural cells and brain organoids generated from human pluripotent stem cells and show minimal neuron and astrocyte infection but efficient choroid plexus infection, leading to cell death and functional deficits.